ALTERNATIF KEBIJAKAN PAJAK PERTAMBAHAN NILAI ATAS KONSUMSI ATAU PEMANFAATAN KONTEN DAN JASA DIGITAL DARI PENYEDIA LUAR NEGERI - Miftahudin, Ali; Irawan, Ferry (Scientax, 2020)
The increasing consumption of digital content and services in the era of globalization raises problems related to the collection of Value Added Tax (VAT) on cross-border transactions. One of the problems related to VAT according to the OECD in the BEPS Action Plan 1 is inequality between nonresident and resident tax payer which results in market distortions and substantially impacts on VAT revenue. Nowadays, the Directorate General of Taxes is difficult to supervise VAT on the consumption of digital content and services by consumers instead of Taxable Person. This research discusses supplier, intermediary, and customs collection and current implementation in Australia, Japan and India. This research is a qualitative research with a descriptive case study approach. Supplier and intermediary collection with a simplified registration and collection of VAT for nonresident providers can be a solution to the problems related to VAT on this kind of consumption by consumers.